A systematic literature review of antecedent and reinforcement‐based behavioral feeding interventions without the implementation of escape extinction. (2nd February 2021) - Tereshko, Lisa; Leaf, Justin B.; Weiss, Mary Jane; Rich, Amy; Pistorino, Morgan
Abstract: Restrictive and avoidant patterns of eating behavior can be seen in children with and without a diagnosed disability, and these patterns may then lead to avoidant/restrictive food intake disorder. The three main categories of feeding problems often observed in children are food refusal, refusal to self‐feed, and food selectivity. This literature review includes 21 articles that implemented feeding interventions, without the use of escape extinction or other intrusive interventions, to increase food acceptance. Each article was analyzed across several dimensions (participants, setting, assessments conducted, experimental design, intervention implemented, and outcome and generalization). From this analysis, information regarding the use of antecedent and reinforcement‐based practices for feeding intervention is discussed, as well as limitations in the current literature and suggestions for future research.